Resenha de: The abolition of the Brazilian slave trade - Queiroz, Suely Robles Reis de (Revista de História, 1972)
BETHELL (Leslie). — The Abolition of the Brazilian Slave Trade: Britain, Brasil and the Slave Trade Questions, 1807/1869. Cambridge, 1970. 425 pp.